2019
DOI: 10.3390/toxics7010007
|View full text |Cite
|
Sign up to set email alerts
|

Internal Doses of Glycidol in Children and Estimation of Associated Cancer Risk

Abstract: The general population is exposed to the genotoxic carcinogen glycidol via food containing refined edible oils where glycidol is present in the form of fatty acid esters. In this study, internal (in vivo) doses of glycidol were determined in a cohort of 50 children and in a reference group of 12 adults (non-smokers and smokers). The lifetime in vivo doses and intakes of glycidol were calculated from the levels of the hemoglobin (Hb) adduct N-(2,3-dihydroxypropyl)valine in blood samples from the subjects, demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…The levels of the hemoglobin adducts of acrylamide and glycidamide were about 3-fold and about 2.3-fold higher, respectively, in smokers (n = 255) than those observed in nonsmokers (n = 255) from the European Union. [30] Similarly, Aasa et al [31] reported that there was a considerable difference between the mean levels of hemoglobin adducts resulting from glycidol exposure between non-smoking (10.3 pmol g −1 hemoglobin, n = 6) and smoking adults (23.4 pmol g −1 hemoglobin, n = 6), however, the number of cigarettes per day was not reported. Taken together, despite its presence in the mainstream smoke of cigarettes, [21] smoking seems to contribute less to the overall exposure of furfuryl alcohol compared to respective contributions from that of the other mentioned tobacco smoke components.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of the hemoglobin adducts of acrylamide and glycidamide were about 3-fold and about 2.3-fold higher, respectively, in smokers (n = 255) than those observed in nonsmokers (n = 255) from the European Union. [30] Similarly, Aasa et al [31] reported that there was a considerable difference between the mean levels of hemoglobin adducts resulting from glycidol exposure between non-smoking (10.3 pmol g −1 hemoglobin, n = 6) and smoking adults (23.4 pmol g −1 hemoglobin, n = 6), however, the number of cigarettes per day was not reported. Taken together, despite its presence in the mainstream smoke of cigarettes, [21] smoking seems to contribute less to the overall exposure of furfuryl alcohol compared to respective contributions from that of the other mentioned tobacco smoke components.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study suggest that we are routinely exposed to glycidol fatty acid ester-related compounds from various foods, and that exposure affects the level of hemoglobin adduct of glycidol (DiHOPrVal), which is an indicator of glycidol. Aasa et al reported the glycidol intake for children calculated from the levels of the DiHOPrVal in blood samples [ 26 ]. Monien et al measured DiHOPrVal in maternal blood and cord blood [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean daily glycidol exposure, as estimated from the adduct levels of the participants before the intervention period (background levels of diHOPrVal), was 0.94 µg/kg body weight [ 15 ]. Additionally, diHOPrVal levels were used to estimate a continuous exposure of 1.4 μg/kg/day of glycidol in 50 children aged approximately 12 years old [ 16 ]. These values are significantly higher than the European Food Safety Authority estimates of intake for adults and children.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, allyl alcohol can theoretically be converted to diHOPrVal, and the glyceraldehyde hemoglobin adduct might be converted to diHOPrVal under reducing conditions [ 19 ]. Honda et al reported a positive correlation between intake of one food item (western confectionery) and diHOPrVal levels among the 70 food items and 97 nutrients in a food frequency questionnaire [ 12 ], although Aasa et al did not confirm the importance of sweets intake [ 16 ]. Fructose in western confectionery is metabolized to glyceraldehyde [ 20 ].…”
Section: Introductionmentioning
confidence: 99%